Effects of voluntary wheel running on the kidney at baseline and after ischaemia–reperfusion‐induced acute kidney injury: a strain difference comparison. (11th February 2013) - Moningka, Natasha C.; Cunningham, Jr, Mark W.; Sterling, Myrline; West, Crystal A.; Verlander, Jill W.; Croker, Byron P.; Ahlgren, Joslyn; Hayward, Linda; Baylis, Chris
Key points The impact of exercise on functional proteins critical for proper blood vessel health in the kidney is not well understood. Using rats of different genetic backgrounds, we studied how chronic exercise affects the abundance of specific blood vessel proteins in the kidney, and whether this has any impact on the rat's susceptibility to acute kidney injury. We found that the renal response to exercise is dependent on genetic background, and that in one strain exercise rendered the kidney more vulnerable to acute kidney injury. The vulnerable rats exhibited exercise‐dependent loss of the protective renal proteins critical for proper blood vessel health, while the protected strain showed increases in these protective proteins. Our findings are particularly relevant regarding exercise prescription to kidney disease patients. Abstract Exercise‐induced vascular endothelial adaptations in the kidney are not well understood. Therefore, we investigated the impact of voluntary wheel running (VWR) on the abundance of endothelial nitric oxide synthase (eNOS) and extracellular superoxide dismutase (EC SOD), in kidney and lung, and other SOD isoforms and total antioxidant capacity (TAC), in kidney. We also determined whether VWR influences susceptibility to acute kidney injury (AKI). Male Sprague–Dawley and Fisher 344 rats, VWR or sedentary for 12 weeks, were subjected to AKI (uninephrectomy (UNX) and 35 min of left kidney ischaemia–24 h reperfusion, IR). We measured glomerular filtration rate (GFR) and renal plasma flow (RPF), and analysed renal structural injury. Running was comparable between strains and VWR reduced body weight. In Sprague–Dawley rats, VWR reduced eNOS and EC SOD, but increased Mn SOD in kidney. Similar changes were seen after 6 weeks of VWR in Sprague–Dawley rats. In Fisher 344 rats, VWR increased eNOS, all SOD isoforms and TAC in kidney. Both strains increased eNOS and EC SOD in lung with VWR. Compared to UNX alone, UNX‐IR injury markedly reduced renal function for both strains; however, in the Sprague–Dawley rats, VWR exacerbated falls in GFR and RPF due to UNX‐IR, whereas in the Fisher 344 rats, GFR was unaffected by VWR. Some indices of renal structural injury due to UNX‐IR tended to be worse in SD vs. F344. Our study demonstrates that genetic background influences the effect of exercise on kidney eNOS and EC SOD, which in turn influence the susceptibility to AKI.